Effects of CSR, Financial Performance, and Good Corporate Governance (GCG) on Increasing the Corporate’s Value - Marheni, Dewi Khornida; Salim, Silvia; Candy (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
Company value, which plays a role in determining the company's position, can be influenced by several factors such as CSR, financial performance, and good corporate governance. The purpose of this study was to determine and analyze the effect of CSR, financial performance, and corporate governance on firm value. The method used in this research is quantitative method. The type of data collection is secondary data obtained from financial reports and sustainability of manufacturing companies in 2018-2022. The data was analyzed using the multiple linear regression method or Multiple Regression Analysis using the STATA application. The results showed that gender diversity has a significant effect on firm value. This research is important to do so that companies know which aspects should be improved in order to advance company value, and it is also important for investors to consider which companies are much better to invest in.